2020
DOI: 10.3389/fnins.2020.00484
|View full text |Cite
|
Sign up to set email alerts
|

Striatal Volume Increase After Six Weeks of Selective Dopamine D2/3 Receptor Blockade in First-Episode, Antipsychotic-Naïve Schizophrenia Patients

Abstract: Andersen et al. Striatal Increase After Dopamine Blockade reductions in hallucinations. Our data demonstrate a clear link between antipsychotic treatment and striatal volume increase in antipsychotic-naïve schizophrenia patients. Moreover, the treatment-induced striatal volume increase appears clinically relevant by correlating to reductions in core symptoms of schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…In 10 studies patients were treated with both FGAs and SGAs after baseline MRI scan ( 14 , 15 , 20 , 28 , 37 , 39 , 47 49 , 52 ). Other 24 studies observed brain changes after treatment with SGAs ( 16 , 17 , 24 27 , 30 36 , 38 , 40 , 41 , 43 46 , 50 , 51 , 53 , 54 ). Only two studies had no clear information of medication ( 29 , 42 ).…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…In 10 studies patients were treated with both FGAs and SGAs after baseline MRI scan ( 14 , 15 , 20 , 28 , 37 , 39 , 47 49 , 52 ). Other 24 studies observed brain changes after treatment with SGAs ( 16 , 17 , 24 27 , 30 36 , 38 , 40 , 41 , 43 46 , 50 , 51 , 53 , 54 ). Only two studies had no clear information of medication ( 29 , 42 ).…”
Section: Resultsmentioning
confidence: 98%
“…All additional studies included 9 structural studies ( 16 , 44 , 48 54 ) and 8 functional studies ( 17 , 40 43 , 45 47 ). Finally, a total of 36 longitudinal studies was included in this review with good quality (mean score = 8.78) ( Supplementary Table 1 ), including 21 studies ( 14 16 , 27 30 , 32 , 33 , 35 37 , 39 , 44 , 48 54 ) on brain structure and 15 studies ( 17 , 20 , 24 26 , 31 , 34 , 38 , 40 43 , 45 47 ) on brain function ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations